Improved production scheduling of a pharmaceutical company - Pacoricuna Cabrera, Eddy (2015)
In a pharmaceutical company were identified the causes of low level of compliance in the production plan, of the constant backlog of lots for manufacturing and the excessive hours-man during the packaging and conditioning processes in the line of non-sterile liquids. After analyzing the main causes of these deficiencies two improvements are proposed: The first is an automatic line that would be responsible for performing the operations of dosing, capping and labeling and the second is a mathematical model that offers a program of production for non-sterile liquid line. The proposed improvements will allow annual savings of S/. 385,925 with a return of investment 1,11 years.